A arte de programar: um encontro criativo e inovador entre a programação científica e a arte computacional - SÉRIO NETO, Franco de Miranda (Universidade Federal do Pará, 2023)
The art of programming: a creative and innovative encounter between scientific programming and computer art is the theme of this research that aims to investigate the potential of computer art to promote creative learning in scientific programming. The main concern of the research was the following question: what potentialities of computer art promote creative learning in scientific programming? Understanding computer art as a promising path for the development of creativity and innovation in scientific programming, this research explored works and the creative processes of computer artists such as Waldemar Cordeiro and Hamid Naderi Yeganeh. As for the research methodology, we adopted the cartography method, inspired by the concept of the authors Deleuze and Guattari (1995), who essentially propose, in the context of intervention research, to follow movements, processes and entanglements in the investigated territories. As discussed by Passos, Kastrup and Escóssia (2015), cartography becomes the very expression of the subjective, of the paths, which is never given a priori, but will be discovered along the process. Thus, the research work becomes an exercise in mapping life and its processes, drawing the forces that move and transform research in the investigated territories. In this way, the movements of a cartography are guided by clues that will allow the researcher-cartographer to do, under the objects of study, an intense observation to understand their formats in a movement of construction and invention. For this research, four clues were selected: intervention research, cartographer attention, monitoring processes and a narrative policy. The narrative policy adopted was inspired by comic books and the cinematographic work Star Wars to create characters whose mission is to explore the territories of scientific programming and computer art. The research is narrated in four episodes. In Episode I, the theoretical references on creative learning are investigated. In Episode II, the creative potential of the Processing language is explored in the context of research. In Episode III, the creative processes of artists Waldemar Cordeiro and Hamid Naderi Yeganeh are mapped in search of connections between scientific programming and computer art, as well as inspiration for authorial productions with Processing - p5.js for the web. In Episode IV, we present the main product of the thesis: the website Arte de programar, with 3D art galleries and interactive content.